Halal pharmaceuticals - Ab Halim, Mustafa 'Afifi; Mohd Kashim, Mohd Izhar Ariff; Mohd Salleh, Mohd Mahyeddin; Nordin, Norhaslinda; Muhammad Husni, Ahmad (Medwell Journal, 2015)
Halal products are fast gaining worldwide recognition as a new benchmark for safety and quality assurance. Products with halal certification are confidently accepted by consumers especially Muslims as well as those of other religions. Undoubtedly halal product industry has been an emerging industry in Malaysia and all over the world. Recognizing the new concept of halal industry presents an opportunity for manufacturers to make better strategies and innovations in producing their products toward halal certification. Today, halal products are not focused only on food but all products including pharmaceuticals. Since most of Malaysian population are Muslims, the Malaysian Standard on halal pharmaceuticals has been launched to ensure that manufacturers comply with the standard to produce them. This article studies on the fatwa related to pharmaceuticals such as usage of drug, gelatine and alcohol in pharmaceutical products. Apart from that, this paper also looks into the Malaysian Standard of Halal Pharmaceutical - General Guidelines, 2010 and other policies and regulations which have been set by the government. The finding shows that there is an unresolved issue of Shari’ah for pharmaceutical products due to the different opinions of fuqaha’. However, there are also many policies and guidelines on halal pharmaceuticals in Malaysia which are good for Muslim consumers.